Vibrational spectra and surface-enhanced resonance Raman scattering of palladium phthalocyanine evaporated films - Gaffo, L.; Constantino, CJL; Moreira, W. C.; Aroca, R. F.; Oliveira, O. N. (Wiley-Blackwell, 2002)
The vibrational spectra of palladium phthalocyanine (PdPc) evaporated thin solid films are reported, including the resonance Raman scattering, surface-enhanced resonance Raman scattering (SERRS) and SERRS mapping of the film surface using micro-Raman spectroscopy with 633 nm laser radiation. SERRS of PdPc was obtained by evaporating an overlayer of Ag nanoparticles on to the PdPc film on glass. The SERRS enhancement factor is estimated as similar to10(4) with reference to PdPc evaporated films on glass. The molecular organization of the PdPc evaporated films was probed using transmission and reflection-absorption infrared spectra. It was established that a random molecular distribution found in PdPc evaporated films is independent of temperature. No evidence of thermal degradation due to thermal annealing was found in the films. Electronic absorption and emission spectra are also discussed. Copyright (C) 2002 John Wiley Sons, Ltd.